Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.32677/ijch.2017.v04.i03.034
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of acute suppurative otitis media with infant feeding position

Abstract: Background: Acute otitis media (AOM) is the most common childhood illness necessitating medical therapy for children younger than 5 years. Long-term and exclusive breastfeeding is associated with protection against AOM. However, faulty feeding position and habits can lead to the occurrence of AOM in infants. Objectives: The aim of this study is to assess the risk of occurrence of AOM with faulty feeding positions during the 1st year of life. Materials and Methods: All breastfed infants <1 year with a provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The results of our study provide valuable information regarding the gender wise distribution of incidence of AOM, age wise distribution of incidence of AOM, association between incidence of AOM and breast feeding position, and association between breast feeding position with maternal educational status. AOM is a commonest illness among childhood with the best incidence in the first year of life, with the peak incidence in the second 6 months in most studies and the frequency gradually declines as the age increases [3]. In our study similar finding is observed, majority cases were found to be between 10-12 followed by 7-9 months of age.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results of our study provide valuable information regarding the gender wise distribution of incidence of AOM, age wise distribution of incidence of AOM, association between incidence of AOM and breast feeding position, and association between breast feeding position with maternal educational status. AOM is a commonest illness among childhood with the best incidence in the first year of life, with the peak incidence in the second 6 months in most studies and the frequency gradually declines as the age increases [3]. In our study similar finding is observed, majority cases were found to be between 10-12 followed by 7-9 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…In our study similar finding is observed, majority cases were found to be between 10-12 followed by 7-9 months of age. A study that was conducted in India also showed that occurrence of AOM was most noteworthy among children of 7-9 months age group [3]. Although prevalence was more among male infants than female infants however it was not statistically significant (p=0.169).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations